Bioreduction with Efficient Recycling of NADPH by Coupled Permeabilized Microorganisms - Zhang, Wei (American Society for Microbiology (ASM), 2009)
The glucose dehydrogenase (GDH) from Bacillus subtilis BGSC 1A1 was cloned and functionally expressed in Escherichia coli BL21(pGDH1) and XL-1 Blue(pGDH1). Controlled permeabilization of recombinant E. coli BL21 and XL-1 Blue with EDTA-toluene under optimized conditions resulted in permeabilized cells with specific activities of 61 and 14 U/g (dry weight) of cells, respectively, for the conversion of NADP(+) to NADPH upon oxidation of glucose. The permeabilized recombinant strains were more active than permeabilized B. subtilis BGSC 1A1, did not exhibit NADPH/NADH oxidase activity, and were useful for regeneration of both NADH and NADPH. Coupling of permeabilized cells of Bacillus pumilus Phe-C3 containing an NADPH-dependent ketoreductase and an E. coli recombinant expressing GDH as a novel biocatalytic system allowed enantioselective reduction of ethyl 3-keto-4,4,4-trifluorobutyrate with efficient recycling of NADPH; a total turnover number (TTN) of 4,200 mol/mol was obtained by using E. coli BL21(pGDH1) as the cofactor-regenerating microorganism with initial addition of 0.005 mM NADP(+). The high TTN obtained is in the practical range for producing fine chemicals. Long-term stability of the permeabilized cell couple and a higher product concentration were demonstrated by 68 h of bioreduction of ethyl 3-keto-4,4,4-trifluorobutyrate with addition of 0.005 mM NADP(+) three times; 50.5 mM (R)-ethyl 3-hydroxy-4,4,4-trifluorobutyrate was obtained with 95% enantiomeric excess, 84% conversion, and an overall TTN of 3,400 mol/mol. Our method results in practical synthesis of (R)-ethyl 3-hydroxy-4,4,4-trifluorobutyrate, and the principle described here is generally applicable to other microbial reductions with cofactor recycling.